PENDEKATAN METODE HACCP (HAZARD ANALYSIS CRITICAL CONTROL POINTS) DAN BAHAN TAMBAHAN MAKANAN PADA KRIPIK SINGKONG YANG DI PRODUKSI OLEH PT. KREASI LUTVI DESA TUNTUNGAN II TAHUN 2014 - Chairul Anwar; wirsal hasan; taufik ashar (Lingkungan dan Kesehatan Kerja, 2014)
ABSTRACT Critical control point food in PT. Kreasi Lutvi aims to ensure food safety system that guarantine clean and safe to eat, so avoid poisoning or diseases such as diarrhea, cholera, dysentry, baccillary, typhoid, fever and soon. The aims of this research to know the critical control point, hygiene, sanitation, phsycal due dilligent as well as food additives in PT. Kreasi Lutvi. The object research in PT. KL Tuntungan II Deli serdang. The method usedi s description to see an overview of sanitation hygiene, critical control point, as well as the physical feasbility of food additives in PT. Kreasi Lutvi. The result of this study indicate that the critical control points in the overall food processing in PT.Kreasi Lutvi a critical control point. So also in the hygiene and sanitation as well as a whole not meet the health requirements in accordance with a qualified health based on Permenkes RI. No.1096/Menkes/PER/VI/2011. That a qualified health if the total score 83. The conclusion of this study is the 6 principles of hygiene and sanitation of food processing do not meet the health requirements, as well as the critical control point which is in a critical control point in the stages of food processing as well as the physical feasibilty test notyet meet health requirements on food additives, too based on the results it is expected that PT.Kreasi Lutvi to further improve sanitation facilities to support hygiene and sanitation of food processing and medical attention handlers so that a very small possibility of contamination of the food.